Winter habitat use of Cabot's Tragopan (Tragopan caboti) in Guangxi, China: Implications for conservation - Yongjian Bei; Jieling Lai; Linzhuang Bai; Siwen Bin; Yunyan Qin; Jianxun Chen; Hui Gao; Yongjie Huang (Global Ecology and Conservation, 2025)
Understanding habitat use by endangered species and its spatial variability is imperative for developing effective conservation strategies. Currently little is known about the habitat use of Cabot’s Tragopan (Tragopan caboti) in southern China. In this study, we employed infrared cameras to monitor the wintering Cabot's Tragopan in four nature reserves in Guangxi (Gupo Mountain (GPM), Haiyang Mountain (HYM), Xiling Mountain (XLM), and Yindian Mountain (YDM) Nature Reserves), covering the entire distribution of Cabot's Tragopan in Guangxi, China. We investigated the local habitat characteristics at each monitoring site and used landscape-scale data to explore winter habitat use and its spatial variability across different reserves. The results indicated that human disturbance intensity was a key factor in winter habitat use by Cabot's Tragopan, exerting a significantly negative impact. Cabot's Tragopans tended to select habitats at higher elevations and preferred broadleaf forests while avoiding coniferous forests. The key habitat characteristics for Cabot's Tragopans in the GPM Nature Reserve were distinctly different from those in the other three nature reserves, characterized by lower levels of four important factors: human disturbance intensity, elevation, area percentage of broadleaf forest within a 300 m radius, and area percentage of coniferous forest within a 500 m radius. This suggests that the demand for elevated and broadleaf forests can be reduced in areas with low human disturbance. Our study accentuates high sensitivity of Cabot's Tragopan to human disturbance, establishing strict regulations for entering mountains near and/or in nature reserves, coupled with the protection and restoration of natural broadleaf forests, are crucial for the conservation of Cabot's Tragopan.